2020
DOI: 10.1101/2020.12.05.412882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomics of altitude-associated wing shape in two tropical butterflies

Abstract: Understanding how organisms adapt to their local environment is central to evolution. With new whole-genome sequencing technologies and the explosion of data, deciphering the genomic basis of complex traits that are ecologically relevant is becoming increasingly feasible. Here we study the genomic basis of wing shape in two Neotropical butterflies that inhabit large geographical ranges. Heliconius butterflies at high elevations have been shown to generally have rounder wings than those in the lowlands. We rear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 98 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…With so many potential targets of selection within SHDRs, we do not attempt to infer biological function or adaptive significance from the whole gene set. Instead, we checked for overlaps with regions recently associated with wing shape variation across an altitudinal cline of Southern Ecuador in H. erato and H. melpomene 34 . Rounder wings are generally associated with high altitude across 13 species of Heliconius 33 and subtle altitudeassociated wing shape variation is highly heritable in H. erato and H. melpomene 34 .…”
Section: Known Genes Of Interest Overlap With Shdrsmentioning
confidence: 99%
See 4 more Smart Citations
“…With so many potential targets of selection within SHDRs, we do not attempt to infer biological function or adaptive significance from the whole gene set. Instead, we checked for overlaps with regions recently associated with wing shape variation across an altitudinal cline of Southern Ecuador in H. erato and H. melpomene 34 . Rounder wings are generally associated with high altitude across 13 species of Heliconius 33 and subtle altitudeassociated wing shape variation is highly heritable in H. erato and H. melpomene 34 .…”
Section: Known Genes Of Interest Overlap With Shdrsmentioning
confidence: 99%
“…Instead, we checked for overlaps with regions recently associated with wing shape variation across an altitudinal cline of Southern Ecuador in H. erato and H. melpomene 34 . Rounder wings are generally associated with high altitude across 13 species of Heliconius 33 and subtle altitudeassociated wing shape variation is highly heritable in H. erato and H. melpomene 34 . We found that five out of 12 previously identified candidate wing shape loci 34 , overlapped with SHDRs in H. erato, three of which corresponded to SHDRs detected in all transects.…”
Section: Known Genes Of Interest Overlap With Shdrsmentioning
confidence: 99%
See 3 more Smart Citations